Soil bacteria hold the key to root cluster formation - Lamont, Byron; Perez-Fernandez, M.; Rodriguez-Sanchez, J. (Wiley-Blackwell Publishing Ltd., 2015)
Root clusters are bunches of hairy rootlets that enhance nutrient uptake among many plants. Since first being reported in 1974, the involvement of rhizobacteria in their formation has received conflicting support. Attempts to identify specific causative organisms have failed and their role has remained speculative. We set up a gnotobiotic experiment using two root-clustered species, Viminaria juncea (Fabaceae) and Hakea laurina (Proteaceae), and inoculated them with two plant-growth-promoting rhizobacteria (PGPR), Bradyrhizobium elkanii and Bacillus mageratium, that produceindole-3-acetic-acid (IAA). Plants were suspended in water culture with four combinations of nitrogen and phosphorus. Clusters only developed in the presence of PGPR in two treatments, were greatly enhanced in another four, suppressed in five, and unaffected in five. Nitrogen amendment was associated with a higher density of clusters. Bradyrhizobium promoted cluster formation in Hakea, whereas Bacillus promoted cluster formation in Viminaria and suppressed it in Hakea. Greater root cluster numbers were due either to a larger root system induced by PGPR (indirect resource effect) and/or to more clusters per unit length of parent root (direct morphogenetic effect). The results are interpreted in terms of greater IAA production by Bradyrhizobium than Bacillus and greater sensitivity of Viminaria to IAA than Hakea.